PHENOMENON OF UNDERAGE MARRIAGE: A STUDY IN THE PERSPECTIVE OF LAW AND ISLAM - MIEKE ANGGRAENI DEWI; KUSWARINI KUSWARINI; WIDIATI DWI WINARNI (GANEC SWARA, 2024)
Marriage is a bond that gives rise to a family as one of the elements in social and state life, regulated by legal rules, both Islamic law and positive law (state law). In marriage laws, the age limit for marriage has been stipulated (material requirements), one of which is the provision regarding the minimum age limit set forth in Article 7 paragraph (1) of Law Number 1 of 1974 concerning Marriage. In reality, many marriages are conducted below the provisions of marriage laws, which have long been happening not only in urban areas but also in remote areas. The reasons vary, due to economic issues, low education, understanding of cultural and certain religious values, and others. Most Muslim scholars agree that underage marriage is permissible with certain conditions. Thus, supported by the fact that our legal system does not criminalize such marriages and that this issue remains a subject of debate in society, underage marriages should not be criminalized in future law